2014
DOI: 10.1089/jop.2014.0020
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells Without c-Myc Ameliorate Retinal Oxidative Damage via Paracrine Effects and Reduced Oxidative Stress in Rats

Abstract: Purpose: To investigate the efficacy and mechanisms of non-c-Myc induced pluripotent stem cell (iPSC) transplantation in a rat model of retinal oxidative damage. Methods: Paraquat was intravitreously injected into Sprague-Dawley rats. After non-c-Myc iPSC transplantation, retinal function was evaluated by electroretinograms (ERGs). The generation of reactive oxygen species (ROS) was determined by lucigenin-and luminol-enhanced chemiluminescence. The expression of brainderived neurotrophic factor, ciliary neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Furthermore, a significant increase in hmox‐1 and txn‐2 mRNA expression was seen in both hUCBMSCs treated groups with significantly higher levels in the intravitreal group compared to the intravenous group. In line with our results, Fang et al recorded a significant decrease in nitrotyrosine in stem cell treated group and mentioned that the therapeutic mechanisms of stem cell transplantation were partially due to reduced retinal oxidative stress . In addition, Cai at al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, a significant increase in hmox‐1 and txn‐2 mRNA expression was seen in both hUCBMSCs treated groups with significantly higher levels in the intravitreal group compared to the intravenous group. In line with our results, Fang et al recorded a significant decrease in nitrotyrosine in stem cell treated group and mentioned that the therapeutic mechanisms of stem cell transplantation were partially due to reduced retinal oxidative stress . In addition, Cai at al.…”
Section: Discussionsupporting
confidence: 91%
“…Fang et al recorded similar results. They attributed the functional improvements observed after stem cell transplantation to bFGF as its secretion occurred from days 7 to 21, concurrent with periods of functional improvement . Moreover, Zhang and Wang found that the expression of bFGF by MSCs continued for several months .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, iPSC-based therapy was shown to decrease high tidal volume ventilation-induced inflammation, oxidative stress, and MIP-2 production via the inhibition of the NF-κB/NKRF pathways. Notably, the iPSC-conditioned medium revealed beneficial effects equal to those of iPSCs [ 32 , 33 ]. In our study, the phosphorylated level of the NF-κB p65 subunit was lower in rats receiving iPSC-based therapy than rats treated with MCT alone ( Fig 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Murine iPSCs were kindly provided by Dr. Shih-Hwa Chiou [ 32 34 ]. M ouse e mbryonic f ibroblasts (MEFs), used as feeder cells, were cultured to confluence and subsequently treated with 10 μg/mL mitomycin C for 3 h to inhibit proliferation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation